Identification of pelvic organ prolapse risk susceptibility gene SNP locus in Xinjiang women - Abulaizi, Aibibuhan·; Abula, Abudoureyimu·; Ababaikeli, Gulina·; Wan, Xiaohui; Du, Rong; Zhakeer, Adilai (International Urogynecology Journal, 2020)
Introduction and hypothesis Susceptibility genes play an important role and have regional specificity in the occurrence of pelvic organ prolapse (POP). This study aims to identify POP susceptibility genes and their loci in ethnic minorities with different genetic backgrounds from Xinjiang in China, providing a theoretical basis for early POP diagnosis, treatment and prevention. Methods Genomic DNA from peripheral blood of 196 patients was prepared; there were 88 POP patients and 108 non-pelvic floor dysfunction patients. We selected 16 different susceptibility gene single-nucleotide polymorphism (SNP) loci, which had been identified as associated with POP risk by researchers in other countries, and carried out genotyping through the Snapshot reaction. The allele and genotype frequencies, odds ratio (OR) and 95% confidence interval (CI) were analyzed using SPSS 17.0 software. Results The genotypic and allelic distributions demonstrated significant differences between the patients and the control subjects in the group of minority women, details are as follows: ESR1 rs17847075 AG: OR = 2.738, 95% CI = 1.067–7.025, P = 0.041; ESR1 rs2234693 TC: OR = 2.99, 95% CI = 1.163–7.684, P = 0.024; ZFAT rs1036819 CC: OR = 10.286, 95% CI = 1.158–91.386, P = 0.036; allele C: OR = 2.212, 95% CI = 1.146–4.269; P = 0.02; FBLN5 rs12589592 AA: OR = 0.111, 95% CI = 0.013–0.952, P = 0.029; allele A: OR = 0.482, 95% CI = 0.254–0.913, P = 0.028. Conclusions ESR1 rs17847075 genotype AG in the dominant model ( P = 0.008) or heterozygous model ( P = 0.045), ES R1 rs2234693 genotype TC in the dominant model ( P = 0.008) or heterozygous model ( P = 0.028), and ZFAT rs1036819 genotype CC and allele C in the recessive model ( P = 0.042) were significantly associated with POP risk in Xinjiang woman.